PRINCIPLES OF TEACHING DIFFERENT AGE GROUPS - Dilnozaxon Mahmudova (TADQIQOTLAR.UZ, 2024)
ABSTRACT: This article studies the progress of teaching foreign languages in different age groups and the role of different teaching principles in this process, as well as problems that that learners come across in communication and speaking practice and appropriate solutions for them.